The Influence of Digital Financial Literacy and E-Payment Adoption on Financial Inclusion with Financial Behavior as a Mediating Variable in Generation Z - Indah Saputri; Mayaliza Mayaliza; Agustina Agustina (Greenation International Journal of Tourism and Management, 2026)
The increasing development of digital financial technology has transformed financial access and behavior, particularly among younger generations who are highly engaged with digital financial services. In Indonesia, this transformation is also accompanied by efforts to expand financial inclusion  however, challenges remain due to uneven levels of financial literacy across society. This research intends to explore how Digital Financial Literacy and the use of E-Payment systems impact Financial Inclusion, with Financial Behavior acting as a mediating factor for Generation Z. The motivation for this study arises from the noticeable disparity betweens the high rate of financial inclusion (85. 10%) and the low level of financial literacy (49. 68%) observed in Indonesia. A quantitative methodology is employed, using an associative-causal framework and Structural Equations Models (SEM) based on Partial Least Squares (PLS), analyzed through SmartPLS with data from 422 respondents from Generation Z. Findings indicate that Digital Financial Literacy positively and significantly influences both Financial Behavior and Financial Inclusion. While E-Payment Adoption also positively and significantly impacts Financial Inclusion, it does not significantly affect Financial Behavior. Additionally, Financial Behavior does not significantly influence Financial Inclusion, meaning it does not mediate the effectss of the two independent variables on Financial Inclusion. Overall, the findings reveal that digital financial literacy and the adoption of electronic payments play a significant role in enhancing financial inclusion, yet financial behavior does not significantly mediate this connection.